Translation Of Thought, Literature, And Philosophy From Al-jahiz’s Perspective: Possible Or Impossible - Abdul khaliq Esa (Al-Lisaniyyat)
Al-Jahiz is considered an outstanding Arab writer and scholar who wrote on wide range of topics and provided many insightful opinions on many topics to scientists and literary men .One of the important topics he dealt with was translation and translators. He talked about the translators regarding their knowledge of the field they are translating and their knowledge in the source language and the target language as well. Al-Jahiz pointed out that there is a conflict between the source language and the target language. Each tries to exert an influence on the other. Al-Jahiz discussed how the type of the science to be translated and how the insufficient number of translators who translated in such a field affect the translator’s work. This study investigates his opinion regarding aforementioned matter, and his argument about it will be based on examples of translated texts which were translated during the Abbasid era.